Solution thermodynamics and preferential solvation of 3-chloro-N-phenyl-phthalimide in acetone + methanol mixtures (2016)
The thermodynamic properties of the 3-chloro-N-phenyl-phthalimide in acetone + methanol cosolvent mixtures were obtained from solubility data report in literature. The solubility was higher in near acetone and lower in pure methanol at all temperatures st